Perfect people, happier lives? When the quest for perfection compromises happiness: the roles played by substance use and internet addiction - Maftei, Alexandra; Opariuc-Dan, Cristian (Frontiers in Public Health, 2023)
Building on the Conservation of Resources Theory and the Stress-Coping Model, the present study explored the relationship between perfectionism (rigid, self-critical, narcissistic) and subjective happiness among youth. In this relationship, we also examined the mediating roles of substance use (i.e., drinking and smoking) and Internet addiction symptoms. Our sample comprised 431 Romanian university students aged 18 to 25 (M = 20.50, SD = 1.58), and most of them were females (79.81%, self-reported gender). Participants completed self-reported anonymous scales through a web-based survey at the beginning of 2023. Correlation analysis results indicated that all forms of perfectionism were associated with Internet addiction symptoms. Self-critical and narcissistic perfectionism and drinking, smoking, and Internet addiction symptoms were negatively associated with subjective happiness. Path analysis suggested that health-risk behaviors completely mediated the effect of perfectionism on subjective happiness. High levels of perfectionism were associated with high levels of health-risk behaviors, and high levels of addictive behaviors were associated with low levels of subjective happiness. We discuss the present findings considering their practical use regarding students' subjective happiness.